APPROACHES TO STUDYING THE ESSENCE OF ORAL SPEECH ARGUMENTATION (TAMADDUN NURI JURNALI, 2025)
This paper examines various approaches to the study of argumentation: cognitive, epistemological, logical-structural, discursive, dialectical, and pragma-dialectical. It analyzes their strengths and weaknesses, as well as the interrelationships between them. The work is based on an analysis of scholarly works by leading experts in the field of argumentation. Particular attention is  paid to the role of argumentation in communicative processes and its influence on opinion formation.